Microwave-Assisted Synthesis of Modified Glycidyl Methacrylate–Ethyl Methacrylate Oligomers, Their Physico-Chemical and Biological Characteristics - Adam Chyzy; Damian Pawelski; Vladyslav Vivcharenko; Agata Przekora; Michael Bratychak; Olena Astakhova; Joanna Breczko; Pawel Drozdzal; Marta E. Plonska-Brzezinska (Molecules, 2022)
In this study, well-known oligomers containing ethyl methacrylate (EMA) and glycidyl methacrylate (GMA) components for the synthesis of the oligomeric network [P(EMA)-co-(GMA)] were used. In order to change the hydrophobic character of the [P(EMA)-co-(GMA)] to a more hydrophilic one, the oligomeric chain was functionalized with ethanolamine, xylitol (Xyl), and L-ornithine. The oligomeric materials were characterized by nuclear magnetic resonance and Fourier transform infrared spectroscopy, scanning electron microscopy, and differential thermogravimetric analysis. In the final stage, thanks to the large amount of -OH groups, it was possible to obtain a three-dimensional hydrogel (HG) network. The HGs were used as a matrix for the immobilization of methylene blue, which was chosen as a model compound of active substances, the release of which from the matrix was examined using spectrophotometric detection. The cytotoxic test was performed using fluid extracts of the HGs and human skin fibroblasts. The cell culture experiment showed that only [P(EMA)-co-(GMA)] and [P(EMA)-co-(GMA)]-Xyl have the potential to be used in biomedical applications. The studies revealed that the obtained HGs were porous and non-cytotoxic, which gives them the opportunity to possess great potential for use as an oligomeric network for drug reservoirs in in vitro application.